2014
DOI: 10.1155/2014/718918
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Formation of Barium Titanate Nanodendrites

Abstract: The barium titanate (BaTiO3) nanoparticles with novel dendrite-like structures have been successfully fabricated via a simple coprecipitation method, the so-called BaTiO3nanodendrites (BTNDs). This method was remarkable, fast, simple, and scalable. The growth solution is prepared by barium chloride (BaCl2), titanium tetrachloride (TiCl4), and oxalic acid. The shape and size of BaTiO3depend on the amount of added BaCl2solvent. To investigate the influence of amount of BaCl2on BTNDs, the amount of BaCl2was varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Ulfa et al studied how temperature and time holding affected the dielectric characteristics of barium titanate using the coprecipitation process, which was then characterised using x-ray diffraction, and scanning electron microscopy was, barium titanate was found to have a perovskite structure in its ideal single phase, (Ulfa et al, 2020). A novel formation of barium titanate Nano dendrites was investigated by C. Huang et al, (2014) using co-precipitation, the addition of BaCl2 solvent is a factor to the shape and size of BaTiO3, also BaCl2 has an effect on crystalline size, morphology and emergence of dendrite-like structures. (C. Huang et al, 2014).…”
Section: Coprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ulfa et al studied how temperature and time holding affected the dielectric characteristics of barium titanate using the coprecipitation process, which was then characterised using x-ray diffraction, and scanning electron microscopy was, barium titanate was found to have a perovskite structure in its ideal single phase, (Ulfa et al, 2020). A novel formation of barium titanate Nano dendrites was investigated by C. Huang et al, (2014) using co-precipitation, the addition of BaCl2 solvent is a factor to the shape and size of BaTiO3, also BaCl2 has an effect on crystalline size, morphology and emergence of dendrite-like structures. (C. Huang et al, 2014).…”
Section: Coprecipitationmentioning
confidence: 99%
“…A novel formation of barium titanate Nano dendrites was investigated by C. Huang et al, (2014) using co-precipitation, the addition of BaCl2 solvent is a factor to the shape and size of BaTiO3, also BaCl2 has an effect on crystalline size, morphology and emergence of dendrite-like structures. (C. Huang et al, 2014). Solid-state reaction and co-precipitation methods was used to detect the consequence of powder preparation on the PTCR characteristics of barium titanate, it was concluded that coprecipitation process produce a greater PTCR features and superior repeatability of prepared samples and low temperature resistance, (Chatterjee, n.d.).…”
Section: Coprecipitationmentioning
confidence: 99%
“…Numerous methods have been used to synthesize BST nanostructures, including hydrothermal approaches [15], sol-gel [16], Chemical deposition [17], ball milling [18], Solvothermal [19], co-precipitation [20], Neutron diffraction [21], Tartrate precursor [22], Blinder jetting [23], and solid-state technique [24]. Researchers have experimented with BT and BST in the presence of a variety of dopants, including Bi [25], Ca [26], Dy [27], Er [28], Eu [29], Fe [30], Ho [31], Hf [32], La [33], Nb [34], Rh [35], Sb [36], Sn [37], V [18], Y [38], Zn [39], and Zr [40].…”
Section: Introductionmentioning
confidence: 99%